The Educational Bias in Commuting Patterns: Micro-Evidence for the Netherlands - Stefan P.T. Groot; Henri L.F. de Groot; Paolo Veneri (Tinbergen Institute, 2012)
This study analyses the relation between education and commuting behaviour of Dutch workers. Results show that, ceteris paribus, higher educated workers commute further, both in terms of distance and time. In addition, higher educated workers are more frequent users of public transport and of bicycles. Furthermore, we find that higher educated workers are relatively more likely to commute towards agglomerated areas and areas that pay relatively high wages, while they are more likely to live in and commute from areas with higher land rents.
urn:NBN:nl:ui:31-1871/38499
Keywords: R12; R21; R23; 330; commuting; education; urban amenities; agglomeration; Pendelverkehr; Bildungsniveau; Agglomerationseffekt; Niederlande